Spatiotemporal Comparisons Between Elite and High-Level 60 m Hurdlers - González-Frutos, Pablo; Veiga, Santiago; Mallo, Javier; Navarro, Enrique (Frontiers in Psychology, 2019)
Despite the existence of literature on the athletics hurdles event, no previous studies have examined the kinematic behavior of athletes along the race. The aims of the present research were (1) to compare the kinematic parameters of elite and high-level hurdlers (men and women) in the approach run, hurdles-unit and run-in phases and (2) to relate these parameters to the 60m end race results. Split times, step lengths, step widths, step times, contact times and flight times were calculated for the 60 m hurdlers (n=110) who participated in the 44th Spanish Indoor Championship and in the 12th IAAF World Indoor Championship. Both male and female elite-level hurdlers obtained shorter split times than high-level hurdlers in the approach run (δ 0.14 ± 0.01 s and 0.18 ± 0.02 s, respectively), the hurdles-unit (δ 0.11 ± 0.01 s and 0.13 ± 0.01 s, respectively) and the run-in (δ 0.10 ± 0.01 s and 0.20 ± 0.02 s, respectively) race phases. Elite-level male athletes also presented lower step lengths in the approach run phase (δ 0.01 ± 0.00 m), greater take-off distances (δ 0.10 ± 0.03 m) and shorter landing distances (δ 0.17 ± 0.05 m) than high-level athletes, although elite-level female hurdlers only showed longer landing step lenght (δ 0.07 ± 0.02 m) than high-level athletes. Finally, in the run-in phase, elite-level hurdlers showed longer step lengths than high-level hurdlers (male: δ 0.09 ± 0.03 m; female: δ 0.11 ± 0.03 m). Step times, contact times and flight times were also different between both levels of performane in most of the race phases. Correlational analysis with the race result showed large (r>0.5), very large (r>0.7) or mearly perfect (r>0.9) relationships for most of the mentioned kinematic parameters. These results confirm the importance of some variables already studied (contact time of take-off, hurdle flight time and take-off and landing distances) to which other unknown variables as the step, contact and flight times in most of the race phases could be added to bring light to the hurdles event performance.